Underage Perpetrators and Victims of Crime According to a Legal Perspective - Ayu Aprilliani; Junifer Dame Panjaitan (Jurnal Restorasi : Hukum dan Politik, 2023)
How does the law view minors through the lens of justice, where these children are perpetrators of criminal acts who must face trials in criminal cases? Also to understand the procedures, flow and process in carrying out trials in child criminal cases. Apart from that, of course it is to analyze the comparison of various differences that will arise from trials of child criminal cases with trials of normal/adult people. The type of research used is the normative juridical method, which is one of various types of research that utilizes statutory regulations.Normative juridical research or what is more familiarly known as doctrinal research aims at all written rules and includes research that is closely related to books, papers, writings and libraries to produce various kinds of data, both of which are secondary in nature. the place where it is located or in the library. In special juvenile justice, there are many differences in how the law treats and views defendants. The trials carried out for the children themselves are more family friendly and carried out briefly. Carrying out trials on children is different from carrying out regular trials on adults. In juvenile justice, the method used is restorative justice, especially criminal acts which of course involve the perpetrator, the victim, the perpetrator's family and the victim's family, as well as the participation of other stakeholders, who will then work together to find a fair solution while remaining focused on recovery. original condition and no motive for revenge.